Neuroprotective effects and possible mechanisms of berberine in animal models of Alzheimer’s disease: a systematic review and meta-analysis - Dan, Lijuan; Hao, Yanwei; Li, Jiaxin; Wang, Tianyuan; Zhao, Weiwei; Wang, Hui; Qiao, Liyan; Xie, Peijun (Frontiers in Pharmacology, 2024)
Recently, multiple preclinical studies have reported the beneficial effect of berberine in the treatment of Alzheimer's disease (AD). Nevertheless, the neuroprotective effects and possible mechanisms of berberine against AD are not universally recognized. This study aimed to conduct a systematic review and meta-analysis by integrating relevant animal studies to assess the neuroprotective effects and potential mechanisms of berberine on AD.We systematically searched PubMed, Embase, Scopus and Web of Science databases that reported the effects of berberine on AD models up to February 1, 2023. The escape latency, times of crossing platform, time spent in the target quadrant and prooligomerized amyloid beta 42 (Aβ1-42) were included as primary outcomes. The secondary outcomes were the Tau-ps 204, Tau-ps 404, β-site of APP cleaving enzyme (BACE1), amyloid precursor protein (APP), acetylcholine esterase (AChE), tumor necrosis factor ⍺ (TNF-α), interleukin 1β (IL-1β), IL-6, nitric oxide (NO), glial fibrillary acidic protein (GFAP), malonaldehyde (MDA), glutathione S-transferase (GST), glutathione (GSH), glutathione peroxidase (GPx), Beclin-1 and neuronal apoptosis cells. This meta-analysis was conducted using RevMan 5.4 and STATA 15.1. The SYRCLE's risk of bias tool was used to assess the methodological quality.Twenty-two studies and 453 animals were included in the analysis. The overall results showed that berberine significantly shortened the escape latency (P < 0.00001), increased times of crossing platform (P < 0.00001) and time spent in the target quadrant (P < 0.00001), decreased Aβ1-42 deposition (P < 0.00001), Tau-ps 202 (P < 0.00001) and Tau-ps 404 (P = 0.002), and improved BACE1, APP, AChE, Beclin-1, neuronal apoptosis cells, oxidative stress and inflammation levels.Berberine may be a promising drug for the treatment of AD based on preclinical evidence (especially when the dose was 5-260 mg/kg). The potential mechanisms for these protective effects may be closely related to anti-neuroinflammation, antioxidative stress, modulation of autophagy, inhibition of neuronal apoptosis and protection of cholinergic system. However, these results may be limited by the quality of existing research. Larger and methodologically more rigorous preclinical research are needed to provide more convincing evidence.